2018
DOI: 10.1093/bjsw/bcx143
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Personal and Critical-Thinking Capabilities in Those about to Enter Qualified Social Work: A Six-Centre Study

Abstract: The 'Process' of intervention is understood to be fundamental to social workevident in, for example, the literature on reflexivity. Little work though has focused on the detailed excavation of the cognitive processes of reasoning in decision making. This is widely recognized as requiring considerable analytic and critical abilities. Although this is long-established, its importance is contemporarily apparent at policy level from the rationale underlying current initiatives such as Frontline. However, it is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…On a more positive note, Sheppard et al (2018) also found that social work graduands scored significantly higher on altruism, insight and compassion than the UK normative sample. Alongside this, there is well documented evidence that social attitudes in Britain are increasingly tolerant in respect of same-sex relationships and the right to choose on issues like euthanasia, abortion and how we live our personal lives (NatCen, 2017).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…On a more positive note, Sheppard et al (2018) also found that social work graduands scored significantly higher on altruism, insight and compassion than the UK normative sample. Alongside this, there is well documented evidence that social attitudes in Britain are increasingly tolerant in respect of same-sex relationships and the right to choose on issues like euthanasia, abortion and how we live our personal lives (NatCen, 2017).…”
Section: Introductionmentioning
confidence: 77%
“…Furthermore, Sheppard and Charles (2017) found that, in a study of four social work programmes, critical thinking ability was not predictive of success on the students' social work undergraduate degrees. Sheppard et al (2018) undertook a further study of twelve social work programmes in England and Wales and found that on measures of critical thinking ability social work granduands were significantly poorer than a UK normative population sample. They also scored significantly lower on assertiveness which resonates with the practice educators in Norstrand's (2017, p.486) study who made a common observation that young 'students could be too passive and "couldn't even make a phone call and so on"'.…”
Section: Introductionmentioning
confidence: 99%
“…NQSWs were compassionate and empathetic, but individual-level values concerned with interpersonal relationships quite clearly dominated. Sheppard et al (2018), in a study of newly qualified social workers from twelve social work programmes, found that the students scored significantly lower than a UK normative sample on tests of critical thinking ability and assertiveness.…”
Section: Neoliberalism In Social Workmentioning
confidence: 91%
“…These are perhaps not the 'minefield' actions of Quninlan's description, but they do take courage and assertiveness. Given that Sheppard et al (2018) found that social work graduands scored more poorly than a UK normative sample on assertiveness measures, the picture is not hopeful. Oliver et al (2017) designed a learning activity around encouraging students to have a difficult conversation, to counteract the tendency of students feeling unable to speak up.…”
Section: Moral Couragementioning
confidence: 94%
“…However, Sheppard et al's [78] study of 12 social work programmes in England and Wales suggests that they do not achieve this. Whilst finding that social work graduands scored more highly than a UK population normative sample on interpersonal characteristics such as insight and altruism, the researchers also found that they scored significantly lower than the normative sample on assertiveness and on critical thinking, with approximately one-third of the sample scoring very poorly on critical thinking tests.…”
Section: Critical Thinking In Social Workmentioning
confidence: 99%